Företags försvar vid anklagelser om brott – betydelsen av den nordiska kontexten - Janne Flyghed; Isabel Schoultz (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract In recent years, several Swedish companies have been accused in the media, by NGOs, and via legal proceedings of engaging in criminal activities. Two of these companies, TeliaSonera and Lundin Petroleum have been the focus of substantial public attention. During the years following the revelations that TeliaSonera, a partly state owned telecommunications company, had committed bribery offences in Central Asia, the affair went from a public scandal in Sweden to a legal process in Sweden and abroad. Lundin Petroleum, a family owned oil company accused of participating in crimes against humanity in Sudan, has continuously denied the accusation by using a variety of denials and neutralizations. The current paper analyzes the strategies employed by these two businesses when defending themselves against allegations of criminal acts. Drawing on Stanley Cohen’s (2009) theoretical work on processes of denial and neutralization techniques, we have identified four main techniques used by the two companies to deflect allegations of criminal wrongdoing: literal denial; denial of knowledge; condemning the condemners; and appealing to a higher loyalty. In addition, we identify how the corporations emphasise their “Nordic values” by linking into a post-colonial discourse and justify their behaviour by relativising it. The article contributes to the discussion of neutralization strategies by pointing out the importance of the context in which a defence takes place.